Conservation Contracts and Political Regimes - Bård Harstad; Torben Mideksa (Center for Economic Studies and ifo Institute (CESifo), 2015)
Motivated by tropical deforestation, we analyze (i) a novel theory of resource extraction, (ii) the optimal conservation contract, (iii) when the donor prefers contracting with central rather than local governments, and (iv) how the donor's presence may induce institutional change. Deforestation can be legal or illegal in the model: each district decides how much to protect and how much to extract for sale on a common market. If districts are strong, in that they find protection inexpensive, extraction is sales-driven and districts bene.t if neighbors conserve. If districts are weak, they lose when neighbors conserve since the smaller supply increases the price and the pressure on the resource, and thus also the cost of protection. Consequently, decentralizing authority increases conservation if and only if districts are weak. Contracting with the central authority is socially optimal, but, on the one hand, the donor benefits from contracting with districts if they are weak; on the other hand, districts prefer to decentralize if they are strong. The presence of the donor may lead to a regime change that increases extraction by more than it is reduced by the contract itself.
Keywords: Q34; 330; deforestation; resource extraction; conservation; contracts; centralization; decentralization; externalities; participation constraints; incentive constraints; tropical forests; climate change; REDD; PES